Comparison of the degree of coronal pigmentation in extracted premolars after the application of bi-antibiotic and tri-antibiotic pastes. - Pedro Mejía; María Monterrosa (Universidad de Concepción., 2015)
Objective: To compare the degree of pigmentation in coronal extracted premolars after applying bi-antibiotic and tri-antibiotic pastes. Method: Intentional non-probability sampling. A total of 30 healthy premolars which were extracted for orthodontic reasons and met the inclusion criteria were divided into 2 experimental groups and a control group of 10 teeth each. Group I (G1) was treated with bi-antibiotic paste, group II (G2) with tri- antibiotic paste; and group III or control (G3) was treated with saline solution. Two observers previously calibrated took the initial color sample from each tooth by giving them a value corresponding to the shade guide. After access opening and instrumentation, all teeth received the appropriate medication and color records were taken under the same initial light conditions for 30 days after the procedure. The obtained data were compiled into Excel for further descriptive and inferential analysis with SPSS 19.0. ANOVA test was used with a confidence level of 95%. Results: The degree of pigmentation was 1±0.9 in G1, 12.2±1.2 in G2 and 0.9±0.8 in G3. No statistically significant differences were found between G1 and G3 (p=0.8086), but there was between G1 and G2 (p<0.001), and G2 and G3 (p<0.001). Conclusion: The degree of pigmentation with tri-antibiotic paste was higher than the degree of pigmentation with bi-antibiotic paste used as temporary medication. No difference was found between the degree of pigmentation in the group treated with bi-antibiotic and the control group treated with saline solution. Bi-antibiotic paste did not show pigmentation in the crown of the extracted premolars.